Does Customer Satisfaction Really Lead Company to Financial Success? A Review and Meta-analysis - Suharyanti, Y.; Dewa, D.M.R.T. (International Journal of Industrial Engineering and Engineering Management, 2019)
All the theories about market and marketing research, customer relationship management, and business in general, believe that customer satisfaction is one of the main factors for company financial success. However, a survey on 64 studies shows a wide variation of the correlation between customer satisfaction and financial performance. The correlation coefficients are varied from -0.256 to 0.899. This study applies a meta-analysis on those 64 studiesâ€™ findings to find the true correlation between customer satisfaction and financial performance. The analysis clusters the 64 studies based on year of research, business category observed, and geographical area of research. The result shows that the correlation between customer satisfaction and financial performance is relatively high (0.525) before 1990, becomes confusing (not-significantly correlated) in 1991-2000, increases (0.626) in 2001-2010, and decreases (0.595) after 2011. Based on business category, the two variables are not significantly correlated both in manufacturing industries and in service industries. The two variables are significantly correlated according to the studies conducted in Europe region (0.566) and Asia-Africa (0.657), but could not to be proven significantly correlated in USA region. The insights from the meta-analysis findings are: (1) the customer satisfaction role is change by time as well as the changes of industry environment, so that research on customer satisfaction will always be beneficial; (2) in individualist society like USA, further researches on customer behavior and culture are required to find more clear explanation about the role of customer satisfaction as well as other financial success factors, on the company performance.Â